The globalization of climate change: Amplification of climate-related physical risks through input-output linkages - Stephan Fahr; Richard Senner; Andrea Vismara (European Central Bank (ECB), 2024)
While global supply chains have recently gained attention in the context of the Covid-related crisis as well as the war in Ukraine, their role in transmitting and amplifying climate-related physical risks across countries has received surprisingly little attention. To address this shortcoming, this paper for the first time combines country-level GDP losses due to climate-related physical risks with a global Input-Output model. More specifically, climate-related GDP-at-risk data are used to quantify the potential direct impact of physical risks on GDP at the country or regional level. This direct impact on GDP is then used to shock a global Input-Output (IO) model so that the propagation of the initial shock to country-sectors around the world becomes observable. The findings suggest that direct GDP loss estimates can severely underestimate the ultimate impact of physical risk because trade can lead to losses that are up to 30 times higher in the EA than what looking at the direct impacts would suggest. However, trade can also mitigate losses if substitutability across country-sectors is possible. Future research should (i) develop more granular, holistic, and forward-looking global physical risk data and (ii) examine more closely the role of both partially substitutable outputs, and critical outputs that are less substitutable or not substitutable at all, such as in the food sector.
Keywords: E01; Q54; Q56; F18; 330; Supply chains; physical risk; climate change